Unequal gradients: Sex, skin tone, and intergenerational economic mobility - Luis Monroy-Gómez-Franco; Roberto Vélez Grajales; Gastón Yalonetzky (University of Massachusetts, Department of Economics, 2023)
We study how the intersection between skin tone and sex shapes intergenerational mobility of economic resources in Mexico. Using two recent social mobility surveys, we estimate the rank persistence and transition matrices by sex combined with skin tone groups. First, we find no differences in intergenerational mobility patterns between light-skin men and women. Second, the colorist mobility pattern observed in previous literature affects men and women differently. Namely, while women of intermediate and dark-skin tonalities have a lower expected rank than their light-skin peers, only men of the darkest tonalities suffer from the same penalization. Thirdly, women of intermediate and darker skin tones have lower persistence rates at the top of the distribution of economic resources than men of the same skin tonality.
Keywords: J16; J62; O15; Z13; 330; Stratification economics; Intergenerational mobility; Skin tone; Gender inequality; Mexico